An integrated planning and decision support system (IPDSS) for land consolidation: Theoretical framework and application of the land-redistribution modules - Demetriou, Demetris; Stillwell, John; See, Linda (My University, 2012)
This paper introduces a new planning support system currently under development for land consolidation in Cyprus called LACONISS (LAnd CONsolidation Integrated Support System). The system's structural framework is outlined and the core land redistribution sub-system called LandSpaCES (Land Spatial Consolidation Expert System) is exemplified using a case study. Model evaluation indicates that the results provide a close fit to those derived by independent human experts. Alternative solutions are generated under different evaluation scenarios and sensitivity analysis is used to examine the weights and performance scores of the criteria involved in the process. © 2012 Pion and its Licensors.
Keywords: Cyprus; Expert systems; Genetic algorithms; Land consolidation; Land reallocation; Multicriteria decision methods